Measuring brand awareness as a component of eating habits in children: the development of the IBAI (International Brand Awareness Instrument) Italian version - Franchin, L.; Zobec, F.; Ghidina, et al., M. (Progress in Nutrition, 2012)
The aim of the present work was to develop an instrument that allows to estimate the Italian children’s brand awareness. We developed the IBAI (International Brand Awareness Instrument), an age-appropriate instrument that uses thirty sheets with pictures of food logos to test children’s recall and recognition, and the IBAI-r, a reduced and less time-consuming form of the IBAI (with 12 sheets).The IBAI was presented (Study 1) to a sample of 145 children aged from 6 to 11 years, and after one month the IBAI-r was presented (Study 2) to the same sample. Both instruments allowed to distinguish different kinds of children’s brand awareness and when compared, they resulted to be very consistent.Misurare la conoscenza dei marchi come una componente delle abitudini alimentari dei bambini: lo sviluppo dell'IBAI (International Brand Awareness Instrument) versione italianaRiassuntoLo scopo di questo studio è di sviluppare uno strumento che permetta di stimare la riconoscibilità dei marchi nei bambini italiani. Per testare la memoria e la conoscenza dei bambini, abbiamo creato l’IBAI (International Brand Awareness Instrument), uno strumento composto da trenta schede con immagini di loghi di prodotti alimentari, e l’IBAI-r, una forma ridotta dell’IBAI, composta da 12 schede. L’IBAI è stato presentato ad un campione di 145 bambini, di età compresa tra i 6 e gli 11 anni (studio 1), e dopo un mese, allo stesso campione di bambini, è stato proposto l’IBAI-r (studio2). Entrambi gli strumenti hanno permesso di distinguere livelli di conoscenza dei marchi diversi tra i vari bambini e quando comparate, le differenze risultano essere molto consistenti.